Exposure assessment of urinary deoxynivalenol in pregnant women in Wuhan, China. (September 2022) - Chen, Tingting; Tan, Tianqi; Zhu, Wenwen; Gong, Lin; Yan, Yizhong; Li, Qian; Xiao, Daxiang; Li, Yanan; Yang, Xuefeng; Hao, Liping; Wang, Huaiji; Yang, Nianhong; et al.
Abstract: Deoxynivalenol (DON) is a ubiquitous trichothecene mycotoxin in food. DON and its modified forms can cross the placental barrier and influence the foetus' health. Limited information is available on exposure of dietary DON intake of pregnant women in China recently. We estimated the exposure of dietary DON intake of pregnant women in a large sample size (n = 2534) from China. The total DON (tDON) and free DON (fDON) biomarkers in urine were detected by liquid chromatography–tandem mass spectrometry. The mean concentration of tDON was 34.8 ng/mg creatinine, and the fDON was 15.9 ng/mg creatinine. The estimated exposure of dietary DON intake was 0.96–1.91 μg/kg bw/day, and the difference in exposure of DON between the first and second trimesters was statistically insignificant. Approximately 26%–60% of individuals exceeded the provisional maximum tolerable daily intake (PMTDI). The age, pre-pregnancy BMI, and the sampling seasons may be the risk factor for the occurrence of exceeding PMTDI. This survey is the first exposure biomarker for DON in a large sample size from pregnant women in China. We found that the dietary DON exposure in pregnant women was relatively high and particular concern should be paid to the DON exposure during pregnancy. Graphical abstract: Image 1 Highlights: This is the first study to evaluate pregnant women exposure to DON with indirect measurements in urine samples for over 2000 subjects of a single population. The dietary exposure to DON in pregnant women was relatively high in China and needed to pay particular concern. Provide a new view on the exposure of dietary DON intake of pregnant women in China.